2004
DOI: 10.4049/jimmunol.173.4.2227
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Estrogen Drives Expansion of the CD4+CD25+ Regulatory T Cell Compartment

Abstract: CD4+CD25+ regulatory T cells are crucial to the maintenance of tolerance in normal individuals. However, the factors regulating this cell population and its function are largely unknown. Estrogen has been shown to protect against the development of autoimmune disease, yet the mechanism is not known. We demonstrate that estrogen (17-β-estradiol, E2) is capable of augmenting FoxP3 expression in vitro and in vivo. Treatment of naive mice with E2 increased both CD25+ cell number and FoxP3 expression level. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
336
5
10

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 463 publications
(366 citation statements)
references
References 19 publications
15
336
5
10
Order By: Relevance
“…Our observations regarding 17β-estradiol are in contrast to the general consensus that in the murine system, Tregs are potentiated by 17β-estradiol (16,37,38). Interestingly, under certain inflammatory conditions, human pregnancy levels of 17β-estradiol have been shown to enhance the expression of NF-κB (39), one of the targets for Foxp3 suppression (40), in fact pointing towards a counteracting effect of 17β-estradiol on Tregs, in line with our results.…”
Section: Discussioncontrasting
confidence: 57%
“…Our observations regarding 17β-estradiol are in contrast to the general consensus that in the murine system, Tregs are potentiated by 17β-estradiol (16,37,38). Interestingly, under certain inflammatory conditions, human pregnancy levels of 17β-estradiol have been shown to enhance the expression of NF-κB (39), one of the targets for Foxp3 suppression (40), in fact pointing towards a counteracting effect of 17β-estradiol on Tregs, in line with our results.…”
Section: Discussioncontrasting
confidence: 57%
“…Estrogens are able to shift the T-cell population towards a Th2 phenotype, an activity also confirmed in pilot clinical studies ( [47,83,211,214]) and to influence a subpopulation of Th cells, named T-regulatory cells ( [184,226]). On the other hand, microglia and endothelial cells have probably a more significant role in estrogen action; using irradiation bone marrow chimeras it has been recently shown that the effect of estradiol on clinical EAE and CNS inflammation was not dependent on ERa expression in the peripheral immune system but was conferred by ERa expression on CNS resident cells, namely endothelial and microglial cells ( [80,185]).…”
Section: Estrogens and Multiple Sclerosismentioning
confidence: 59%
“…foxp3 expression and function are under combined control of T cell receptor signaling and multiple cytokines through both transcription and post-transcription regulatory mechanisms 63 . In women, size of Treg cell populations positively correlates with estradiol levels during the luteal cycle and in pregnancy 61 , with estradiol treatment inducing both Treg expansion and Foxp3 expression 64 . Testosterone stimulation causes also a strong increase of Treg cells both in vivo and in vitro, through a mechanism that involves AR recruitment to the foxp3 locus and its enhanced expression 65 .…”
Section: Introduction (Epidemiology)mentioning
confidence: 99%